Obesity Influences the Knee Injury and Osteoarthritis Outcome Score - Larsen, Peter; Engberg, Anne S.; Motahar, Isa; Ostgaard, Svend E.; Elsoe, Rasmus (Joints, 2019)
Purpose The primary aim of this study was to report the outcome of the Knee Injury and Osteoarthritis Outcome Score (KOOS) in obese patients with a body mass index (BMI) > 35.Methods This is a prospective cohort study, including patients referred with the aim of planning bariatric surgery between October 2015 and January 2017. The primary outcome measurement was KOOS. An experienced radiologist obtained and evaluated standard radiological osteoarthritis examinations of the knee joints.Results The mean age was 43.1 years, and ages ranged from 24 to 69 years. The mean BMI was 48.3, and BMI ranged from 35 to 66. Results show that obese patients reported significantly worse in the KOOS subscales pain, activities of daily living, sport, and quality of life (QOL) compared with a reference population, due to nonoverlapping 95% confidence intervals. No significant differences between obese and superobese patients were observed on the KOOS subscales (p > 0.08). The KOOS subscales showed worse outcome with increasing severity of radiological knee osteoarthritis; however, only significant differences were observed for the KOOS subscales sport and QOL (p < 0.05).Conclusion Results imply that the KOOS scores vary significantly with obesity. When utilizing KOOS outcome, considering obesity in the interpretation of outcome is highly recommended.Level of Evidence This is an observational, level III study.
Keywords: KOOS score; joint pain; patient-reported outcomes; obesity; osteoarthritis